A pioneer surgical technique for isolated periodontal defects by “closed” retraction of the papilla: A feasibility study - Apatzidou, Danae Anastasia (Frontiers in Dental Medicine, 2022)
Aim: A pioneer periodontal surgical approach employing the closed surgical technique (CST) in combination with the tissue-engineered biocomplex aimed to gain access to the osseous defect and improve soft-tissue architecture. Methods: The CST was applied in four systemically healthy periodontitis patients/defects who were followed for 12-months. It avoids papilla dissection and retraction of flaps in an open manner thus, suturing is not required. It is designed for the reconstruction of residual isolated periodontal defects and is best indicated in the aesthetic region. It can be applied as a sole treatment approach to facilitate deep instrumentation of the defect, or it could be combined with subgingival application of regenerative materials. Hereby, the biocomplex was applied containing autologous alveolar Bone-Marrow Mesenchymal-Stem-Cells, seeded into collagen scaffolds, enriched with autologous fibrin/platelet lysate. Results: The CST minimised post-operative discomfort and led to improved treatment outcomes with probing pocket depth reduction [average (SD)] of 24.4 (18.5) %, gain in clinical attachment levels of 25.8 (20.1) %, and evidence of remineralisation of the alveolar crest. Conclusion: The CST is a tissue-friendly operation and facilitates subgingival application of biological agents via tunneling the soft-tissues. However, surgical experience is required for non-traumatic manipulation of the gingival tissues during “closed” retraction of the flaps.